The diagnostic performance of indocyanine green for the sentinel node biopsy in prostate cancer: A systematic review and meta-analysis - Siyang Ma; Jianxuan Sun; Jinzhou Xu; Ye An; Mengyao Xu; Chenqian Liu; Sihan Zhang; Lintao Miao; Xingyu Zhong; Na Zeng; Haodong He; Shaogang Wang; et al. (Asian Journal of Urology)
Objective: Almost 15% of prostate cancer (PCa) patients were found to have lymph node metastases (LNMs), which are associated with higher risk of biochemical recurrence. Using indocyanine green (ICG) for the sentinel node biopsy (SNB) before surgery was proposed to detect LNMs in PCa patients. However, its diagnostic performance still remains controversial. This study aimed to investigate the diagnostic performance of ICG for the SNB in PCa. Methods: This systematic review and meta-analysis has been reported in line with the Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines. The protocol has been registered in the International Prospective Register of Systematic Reviews database, and the register number is CRD42023421911. Four bibliographic databases were searched, i.e., PubMed, EMBASE, Cochrane Library, and Web of Science, to retrieve articles studying the diagnostic performance of ICG for the SNB in PCa from the inception to Sep 9, 2023. We calculated the pooled sensitivity, specificity, likelihood ratios, diagnostic odds ratios and their 95% confidence intervals (CIs). Subgroup analyses and meta-regression analyses were also conducted. Results: A total of 17 articles from databases are enrolled in this study. Using lymph node-based data, our results showed that the pooled sensitivity and specificity of applying ICG alone in PCa were 71% (95% CI 52%–85%) and 68% (95% CI 64%–72%), respectively. The pooled sensitivity and specificity of applying ICG-technetium-99m-nanocolloid in PCa were 49% (95% CI 39%–59%) and 69% (95% CI 67%–71%), respectively. Conclusion: The efficacy of using ICG or ICG-technetium-99m-nanocolloid for the SNB in PCa is relatively unsatisfactory. ICG cannot yet substitute extended pelvic lymph node dissection for detecting LNMs accurately. More research or novel tracers are needed to achieve the goal of precise surgery.